2001
DOI: 10.2105/ajph.91.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related risk indicators and preventive screening behaviors among lesbians and bisexual women

Abstract: A B S T R A C TObjectives. This study examined whether lesbians are at increased risk for certain cancers as a result of an accumulation of behavioral risk factors and difficulties in accessing health care.Methods. Prevalence estimates of behavioral risk factors (nulliparity, obesity, smoking, and alcohol use), cancer screening behaviors, and self-reported breast cancer histories derived from 7 independently conducted surveys of lesbians/bisexual women (n = 11 876) were compared with national estimates for wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(61 citation statements)
references
References 38 publications
1
57
2
1
Order By: Relevance
“…There continues to be health disparities among LGBT persons, and LGBT elders specifically. Although a major goal that was highlighted in the Department of Health and Human Services’ Healthy People 2010 was the elimination of health disparities of LGBT individuals, research has suggested that LGBT persons are disproportionately at risk for violent hate crimes, sexually transmitted infections including HIV/AIDS, a variety of mental health conditions (Cochran, 2001; Cochran & Mays, 2000, 2009; Fergusson, Horwood, & Beautrais, 1999; Herek, 2009; Institute of Medicine, 2011; Koh & Ross, 2006), body weight problems (Carlat, Camargo, & Herzog, 1997; Carpenter, 2003; Deputy & Boehmer, 2010), substance use and abuse (Cochran & Mays, 2006; Skinner & Otis, 1996; Stall & Wiley, 1988), smoking (DuRant, Krowchuk, & Sinal, 1998; Stall et al, 1999; Tang et al, 2004), and certain cancers (Cochran et al, 2001; Daling et al, 1987; Dibble, Vanoni, & Miaskowski, 1997; Koblin et al, 1996; Zaritsky & Dibble, 2010). These same health risks were reported by members of the focus groups.…”
Section: Conducting Focus Groups With Lgbt Eldersmentioning
confidence: 99%
“…There continues to be health disparities among LGBT persons, and LGBT elders specifically. Although a major goal that was highlighted in the Department of Health and Human Services’ Healthy People 2010 was the elimination of health disparities of LGBT individuals, research has suggested that LGBT persons are disproportionately at risk for violent hate crimes, sexually transmitted infections including HIV/AIDS, a variety of mental health conditions (Cochran, 2001; Cochran & Mays, 2000, 2009; Fergusson, Horwood, & Beautrais, 1999; Herek, 2009; Institute of Medicine, 2011; Koh & Ross, 2006), body weight problems (Carlat, Camargo, & Herzog, 1997; Carpenter, 2003; Deputy & Boehmer, 2010), substance use and abuse (Cochran & Mays, 2006; Skinner & Otis, 1996; Stall & Wiley, 1988), smoking (DuRant, Krowchuk, & Sinal, 1998; Stall et al, 1999; Tang et al, 2004), and certain cancers (Cochran et al, 2001; Daling et al, 1987; Dibble, Vanoni, & Miaskowski, 1997; Koblin et al, 1996; Zaritsky & Dibble, 2010). These same health risks were reported by members of the focus groups.…”
Section: Conducting Focus Groups With Lgbt Eldersmentioning
confidence: 99%
“…Increased BMI is a risk factor for conditions such as ovarian cancer and PCOS 16, 17. Accordingly, journal articles and public health sources have suggested the combination of increased risk factors may lead to LB women having increased rates of gynaecological conditions 18, 19, 20. Nevertheless, a paucity of research actually measures gynaecological disorder incidence and prevalence in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Because U.S. cancer registries do not collect data on sexual orientation, researchers are unable to definitively assess cervical cancer incidence by sexual orientation identity. Nonetheless, multiple studies have consistently shown that regular Pap test use, which is critical for cervical cancer prevention (20), is lower among lesbians relative to their heterosexual counterparts (2127). Additionally, lesbians may be at higher risk of cervical cancer compared to heterosexual women because of a higher prevalence of smoking (28), a risk factor for cervical cancer morbidity (29), and obesity (30), which has been linked to cervical cancer mortality (31), and a lower prevalence of health insurance (21, 3235) and access to health care (34, 36).…”
Section: Introductionmentioning
confidence: 99%